Diary of a wimpy kid: wrecking ball - Kinney , Jeff (Puffin London, 2021)
In Diary of a Wimpy Kid: Wrecking Ball, Greg Heffley and his family embark on an unexpected adventure as they tackle home renovations that spiral out of control. After receiving an inheritance from a relative, Greg$1 (Bs mother decides it$1 (Bs the perfect time to transform their home, leading to chaotic renovations filled with humorous mishaps and challenges. As Greg navigates the trials of family dynamics, the pressures of school, and the pitfalls of adulthood, he finds himself caught between his desire for a new and improved living space and the absurdity of the situation around him. Kinney$1 (Bs trademark humor and relatable storytelling illuminate the ups and downs of family life, making Wrecking Ball a hilarious and heartfelt exploration of change, chaos, and the meaning of home. Through Greg's witty diary entries and whimsical illustrations, readers are invited to join in the laughter as they witness the Heffleys' hilarious misadventures.s